ESG Reputation Risk under Climate Risk and Global Uncertainty in ASEAN Manufacturing - Meiyanti, Fajar; Adhariani, Desi (Universitas Negeri Gorontalo, 2026)
As the manufacturing sector expands, it faces growing scrutiny regarding its sustainability practices, with Environmental, Social, and Governance (ESG) reputation risk becoming an increasingly critical concern. This study investigates the relationship between climate risk, global uncertainty, and ESG-related reputational risk, using 465 observations from manufacturing companies listed in ASEAN countries between 2021 and 2023. Regression analysis indicates that climate risk has a positive effect on the Reputation Risk Index (RRI). This suggests that firms in regions with greater climate vulnerability are more exposed to ESG reputational challenges. Similarly, global uncertainty is positively and statistically significantly associated with RRI, implying that unpredictable policy and economic conditions can exacerbate reputational risks. These findings underscore the importance of integrating ESG considerations into corporate risk management, particularly in emerging economies with pronounced environmental and institutional risks. Firms are urged to strategically allocate resources toward sustainability initiatives to safeguard their reputation and operational resilience. Additionally, policymakers are encouraged to establish supportive regulatory environments that foster corporate transparency, ESG accountability, and adaptive capacity.